Acute myeloid leukemia with RAM immunophenotype presenting with extensive mesenteric and retroperitoneal lymphadenopathy: A case report and review of the literature. (2022) - Wick, N; Hitto, I; Welder, D; Slone, T; Koduru, P; Fuda, F; Rakheja, D; Weinberg, O
Abstract: Acute myeloid leukemia (AML) with RAM immunophenotype is a rare recently described AML subtype. It is defined by blasts with strong expression of CD56 and weak to absent expression of CD45, HLA-DR....., and CD38 and characterized by significantly worse outcome [1] . Little is known about the clinical presentation and this immunophenotype is not widely recognized in clinical practice. We describe a case of AML with RAM immunophenotype in a 5-year-old male patient with a unique presentation, including extensive mesenteric and retroperitoneal lymphadenopathy. Diagnostic studies included bilateral bone marrow and lymph node biopsies, flow cytometry, cytogenetics, fluorescence in-situ hybridization (FISH), and next generation sequencing. Bone marrow biopsy revealed >90% blasts, positive for CD34, CD117, and CD56 by flow cytometry and immunohistochemistry. Next generation sequencing revealed BCOR loss and CBFA2T3-GLIS2 fusion. Following induction chemotherapy, bone marrow biopsy showed residual disease and a stem cell transplant was performed. The patient relapsed three months after transplant and subsequently passed away eleven months after initial diagnosis. Limited literature is available describing this newly identified AML subset. The RAM immunophenotype has been identified as an independent prognostic factor for relapse rate and overall and disease-free survival [1] . Few case reports are available to characterize the genetic profile, typical presentation, and clinical course of patients with this unique immunophenotype.